10-mer and 9-mer WALK Peptides with Both Antibacterial and Anti-Inflammatory Activities - Su-Jin Kim; Tae-Bong Kang; Dong-Hyuk Kim; Minho Keum; Sung-Hee Lee; Ji-Hun Kim; Sang-Hyuck Lee; Jihoon Kim; Hyuk-Jung Kweon; Jae-Won Park; Beom-Jun Kim; Hyung-Sik Won (MDPI AG, 2022)
Natural antimicrobial peptides (AMPs) are multifunctional host defense peptides (HDPs) that are valuable for various therapeutic applications. In particular, natural and artificial AMPs with dual antibacterial immunomodulatory functions emerged as promising candidates for the development of therapeutic agents to treat infectious inflammation. In an effort to develop useful AMP variants with short lengths and simple amino acid composition, we devised a de novo design strategy to generate a series of model peptide isomer sequences, named WALK peptides, i.e., tryptophan (W)-containing amphipathic-helical (A) leucine (L)/lysine (K) peptides. Here, we generated two groups of WALK peptide isomers: W2L4K4 (WALK244.01~WALK244.10) and W2L4K3 (WALK243.01~WALK243.09). Most showed apparent antibacterial activities against both Gram-positive and Gram-negative bacteria at a concentration of approximately 4 μg/mL along with varied hemolytic activities against human red blood cells. In addition, some exhibited significant anti-inflammatory activities without any significant cytotoxicity in macrophages. Collectively, these results suggest that the two selected peptides, WALK244.04 and WALK243.04, showed promise for the development of antibacterial and anti-inflammatory agents.